Synthesis of Nano alfa-Cellulose-Based Bioplastic from Empty Fruit Bunches of Palm Oil - Benny Rio Fernandez; Rycce Sylviana Pratikha; Sari Farah Dina; Poltak Evencus Hutajulu; Gimelliya Saragih; Dafina Ariza; Indah Fitri Ramadhani; Yosef Boy Wijaya Sinaga (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Cellulose, as a renewable resource, has recently emerged as a primary focus for researchers aiming to develop sustainable biomaterials.  FTIR spectra show that there is no significant difference between them. Apparently, the significant absorption band of cellulose structure at 3300 cm-1 (O-H stretching), 2900 cm-1 (C-H stretching), and at 1022 cm-1 (OCH-O-CH2 cellulose framework). SEM images revealed that changing the surface morphology of the a-cellulose (fibril-shaped) to nano a-cellulose (rod-shaped) resulted in average fiber diameters of 3.07 µm and 2.80 µm, respectively. Particle size distribution of the suspended particles after acid and sonication treatment becomes 380.79 nm. Based on the DTA results, the obtained products have good thermal stability, which decomposes at a temperature 290 oC.　Furthermore, nano a-cellulose was used as a starting material to generate biodegradable plastic with the addition of silica as a filler and glycerin as a plasticizer. Mechanical tests of bioplastics, such as tensile strength, elongation, and modulus of elasticity, show that silica can improve the properties of bioplastics. Finally, the elongation properties of bioplastics meet the Indonesian National Standard (SNI) requirements; however, the tensile strength and modulus of elasticity values require further experiments.